2009
DOI: 10.1002/ppp.662
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt increases in soil temperatures following increased precipitation in a permafrost region, central Lena River basin, Russia

Abstract: Marked increases in active‐layer and upper permafrost temperatures occurred in the central Lena River basin in association with abrupt increases in active‐layer soil moisture following the summer of 2005. The positive trend in soil temperature‐moisture relations was observed at monitoring sites in the Yakutsk area, regardless of vegetation and soil type. The increase in soil temperature appears to have started in response to the large amounts of snow that accumulated in the winter of 2004. Abnormally high pre‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
146
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(154 citation statements)
references
References 21 publications
8
146
0
Order By: Relevance
“…Zhang et al (2001) analyzed long-term changes from the 1890s to 1990s in soil temperatures at Irkutsk, Russia, finding that soil temperature at 40 cm depth increased by up to 9 • C during the winter. Permafrost surface temperatures in northern Alaska have increased by 2-4 • C in the 20th century (Lachenbruch and Marshall, 1986). A warming trend in soil temperature was also found at climate stations across Canada during the 20th century (Chen et al, 2003;Smith et al, 2010;Qian et al, 2011).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Zhang et al (2001) analyzed long-term changes from the 1890s to 1990s in soil temperatures at Irkutsk, Russia, finding that soil temperature at 40 cm depth increased by up to 9 • C during the winter. Permafrost surface temperatures in northern Alaska have increased by 2-4 • C in the 20th century (Lachenbruch and Marshall, 1986). A warming trend in soil temperature was also found at climate stations across Canada during the 20th century (Chen et al, 2003;Smith et al, 2010;Qian et al, 2011).…”
Section: Introductionmentioning
confidence: 75%
“…In reality, soil temperature at the Healy site of interior Alaska has responded to the decreasing SND by a decrease of ALT since the late 1990s (Osterkamp, 2007). By contrast, since 2000 the increased SND in a Siberian taiga forest has significantly contributed to an increase of ALT (Iijima et al, 2010). These site-specific results cannot reliably be extrapolated to large regions.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, this particular region has been subject to very strong rates of lake expansion over the last decades due to several factors, including anthropogenic activity and the change of climatic conditions [43,67]. The recharge of lakes here may be connected to a wetter and warmer climate over the recent decades [34,43,93] and shifting agriculture practices, where meadows and grasslands in alas basins are increasingly managed to produce richer pastures [71]. In addition to the climatic conditions and anthropogenic influence, the local geological conditions seemingly had a strong influence on the lake area changes, where the terraces with ice-rich sediments showed a much more pronounced lake area expansion in comparison to the remaining area.…”
Section: Comparison Of Sites and Prior Studiesmentioning
confidence: 99%
“…On the other hand, we note that a thicker active layer can hold much more water than a frozen layer. Vey et al (2013) have analysed changes in TWS within the active layer (from a depth of 0.1 m to 1.1 m) in Yakutsk, using in situ data collected by Iijima et al (2010); they have found that TWS increased by approximately 5 mm between 2002 and 2010 and that the TWS within the active layer increased by approximately 0.6 mm year −1 . Thus, in our analysis, we considered the effects of permafrost thaw on regional trends in TWS to be small.…”
Section: The Effect Of Permafrost Thawmentioning
confidence: 99%